2023
DOI: 10.5194/nhess-23-693-2023
|View full text |Cite
|
Sign up to set email alerts
|

Increased spatial extent and likelihood of compound long-duration dry and hot events in China, 1961–2014

Abstract: Abstract. Compound dry and hot events can cause aggregated damage compared with isolated hazards. Although increasing attention has been paid to compound dry and hot events, the persistence of such hazards is rarely investigated. Moreover, little attention has been paid to the simultaneous evolution process of such hazards in space and time. Based on observations during 1961–2014, the spatiotemporal characteristics of compound long-duration dry and hot (LDDH) events in China during the summer season are invest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…To validate the downscaled AP from model results, we use the daily temperature, humidity, and wind speed during 2008-2017 from the gridded observational dataset CN05.1 with the resolution of 0.25 • × 0.25 • based on the observational data from more than 2400 surface meteorological stations in China, which are interpolated using the "anomaly approach" (Wu and Gao, 2013). This dataset is widely used and has good performance relative to other reanalysis datasets over China (Zhou et al, 2016;Y. Yang et al, , 2023Yang and Tang, 2023).…”
Section: Scenarios Esm Downscaling Methods and Bias Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the downscaled AP from model results, we use the daily temperature, humidity, and wind speed during 2008-2017 from the gridded observational dataset CN05.1 with the resolution of 0.25 • × 0.25 • based on the observational data from more than 2400 surface meteorological stations in China, which are interpolated using the "anomaly approach" (Wu and Gao, 2013). This dataset is widely used and has good performance relative to other reanalysis datasets over China (Zhou et al, 2016;Y. Yang et al, , 2023Yang and Tang, 2023).…”
Section: Scenarios Esm Downscaling Methods and Bias Correctionmentioning
confidence: 99%
“…This dataset is widely used and has good performance relative to other reanalysis datasets over China (Zhou et al, 2016;Y. Yang et al, , 2023Yang and Tang, 2023). Dynamical downscaling for the four ESM datasets was done with WRFv.3.9.1 with a parameter set used for urban China studies (Wang et al, 2012) in two nested domains at 30 and 10 km resolution over two time slices (2008-2017 and 2060-2069).…”
Section: Scenarios Esm Downscaling Methods and Bias Correctionmentioning
confidence: 99%
“…In addition, this study presents the effect of large-scale climate factors on CADs on an interannual timescale. Although under the background of climate warming, the main factors affecting the production of spring maize have shifted from heat limited to water limited [30,43], and there is a significant increase in the frequency and spatial extent [44,45]. Therefore, the interdecadal shift of CADs needs further research.…”
Section: Analysis Of Physical Mechanismsmentioning
confidence: 99%
“…The combined effect of arid and hot phenomena leads to a large cumulative damage compared to individual dangerous natural phenomena [13]. Also, Hao et al [14] concluded that combined droughts and hot weather events can lead to more serious consequences than individual droughts of the past.…”
Section: Introductionmentioning
confidence: 99%